Solanum nigrum grown in contaminated soil: effect of arbuscular mycorrhizal fungi on zinc accumulation and histolocalisation - Marques, Ana P. G. C. (2010)
Zn tissue accumulation in Solanum nigrum grown in a non-contaminated and a naturally contaminated Zn matrix and the effect of inoculation with different arbuscular mycorrhizal fungi (AMF) on metal uptake were assessed. S. nigrum grown in the contaminated soil always presented higher Zn accumulation in the tissues, accumulating up to 1622 mg Zn kg 1. The presence of both Glomus claroideum and Glomus intraradices enhanced the uptake and accumulation of Zn by S. nigrum (up to 83 and 49% higher Zn accumulation, respectively). The main deposits of the metal were found in the intercellular spaces and in the cell walls of the root tissues, as revealed by autometallography, with the inoculation with different AMF species causing no differences in the location of Zn accumulation. These findings indicate that S. nigrum inoculated with selected heavy metal tolerant AMF presents extracting and accumulating capacities, constituting a potentially suitable remediation method for Zn polluted soils.